2018
DOI: 10.1111/ijpo.12284
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to liquid sweetness in early childhood: artificially‐sweetened and sugar‐sweetened beverage consumption at 4–5 years and risk of overweight and obesity at 7–8 years

Abstract: SummaryBackground: A significant gap exists in longitudinal evidence on early exposure to artificially sweetened beverages (ASBs) and weight outcomes for paediatric populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 28 publications
(59 reference statements)
0
14
0
1
Order By: Relevance
“…Household chaos has been found to be associated with greater infant weight gain at 12 months ( Khatiwada et al, 2018 ). A Scottish study ( Macintyre et al, 2018 ) found some evidence of association with early exposure to artificially sweetened beverages (aged 4–5 years) and risk of obesity (aged 7–8 years). Skouteris et al (2011) suggested that there is still a need for more studies evaluating targeted obesity prevention studies in preschool children.…”
Section: Introductionmentioning
confidence: 99%
“…Household chaos has been found to be associated with greater infant weight gain at 12 months ( Khatiwada et al, 2018 ). A Scottish study ( Macintyre et al, 2018 ) found some evidence of association with early exposure to artificially sweetened beverages (aged 4–5 years) and risk of obesity (aged 7–8 years). Skouteris et al (2011) suggested that there is still a need for more studies evaluating targeted obesity prevention studies in preschool children.…”
Section: Introductionmentioning
confidence: 99%
“…SSB consumption during early childhood may not lead immediately to OWOB, as there may be an age effect. It may take a number of years of SSB consumption before the development of OWOB or metabolic changes associated with obesity [77,[80][81][82]. SSB intake may also be a marker of a food and beverage intake pattern and other lifestyle factors that are associated with obesity.…”
Section: Discussionmentioning
confidence: 99%
“…These habits are in conflict with national and international guidelines because they have been associated with poor dietary patterns [ 22 ]. Consumption of salt, sugar, sweetener and honey in children younger than 2 years of age has been associated with obesity and risk of botulism [ 23 , 24 ]. This is an important consideration for health professionals who have patients reporting BLW practice.…”
Section: Discussionmentioning
confidence: 99%